Effect of a multidisciplinary program with seven color balls on non-communicable diseases prevention in a Muslim community: A real-world study - Phiban, Wichan; Wanitchanon, Kamonwan; Sirithammaphan, Uraiwan; Chaisang, Ubontip; Singkun, Awirut (Edelweiss Applied Science and Technology, 2024)
Prevalence of diabetes and hypertension are increasing. Health promotion is needed for the diseases prevention. The objective of this study was to determine the impact of a multidisciplinary program and a seven-color balls on fasting blood glucose and blood pressure in a Muslim community. A one-group pre-post test of participatory action research was employed. The screening test was administered and assigned a color to each of seven health statuses. All participants made a commitment to improve their weekly performance. They were instructed and practiced for three weeks on six health information topics. Then, each village health volunteer reminded the participants of health information, and a religious leader declared (Kutbah) during Friday prayer that tobacco and alcohol are contrary to Islam. Utilizing frequency and percentage, the study outcome at the end of the program was compared to that at baseline. The results revealed that the mean age of the participants was 33.92 years, with a range of 15 to 82 years. Six months after program finish, 87.5% of those at risk and 93.3% of high risk for hypertension returned to normal blood pressure levels. For FBS level, risk for diabetes participants improved to a normal level by 57.6%, participants who were possibly for diabetes improved to better level by 50%, and third level illness decreased to a lower level by 50%. The program could improve participants’ health status and encourage their self-esteem for health prevention. Prevention of hypertension, and diabetes is essential for promoting individual and community health.